Exploring the moderating effect of government support on actual adoption of e-wallet among mobile phone users in Malaysia - Wong, Wai Jun; Ng, Sue Xin; Lim, Wei Xiong; Chua, Chia Soon (2020)
The study is aimed to examine the moderating effect of government support on actual adoption of e-wallet among mobile phone users in Malaysia. The study determines the presence of moderating effect of government support on the actual adoption of e-wallet by including determinants such as perceived ease of use, perceived usefulness, perceived risk, users’ attitude and intention to adopt e-wallet with the aid of extended Technology Acceptance Model (TAM). The target respondents for this study are the mobile phone users of e-wallet in Malaysia. Our survey involves 434 respondents. Smart Partial Least Squares 3 software (Smart PLS 3) is used to assist in our data analysis along the research. Reliability test, convergent and discriminant validity, and significance of variables are applied in our data analysis. Our results indicate that government support could not moderate the relationship between intention to adopt and actual adoption of e-wallet. However, we find that government support could significantly provide the direct positive influence on mobile phone users’ actual adoption of e-wallet.